2022
DOI: 10.31450/ukrjnd.1(73).2022.07
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid with albuminuria in type 2 diabetic patients with comorbid obesity and/or essential arterial hypertension

Abstract: Abstract. Decompensation of diabetes mellitus type 2 (T2DM), duration of the disease, level of proteinuria, obesity and essential arterial hypertension (AH) play the main role in the development and progress of diabetic nephropathy. The present study aimed to analyze the level of serum uric acid in type 2 diabetic patients with comorbid overweight/obesity and AH and to find its possible correlations with lipid panel data and urinary albumin excretion. Methods. 579 medical records of type 2 diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…Even the smallest degree of albuminuria increases risk for cardiovascular diseases and all-cause death [13]. Marushchak M., et al suggested that serum uric acid level is markedly elevated and positively associated with albuminuria in type 2 diabetic patients with comorbid obesity [14]. Furthermore, the degree of albuminuria is positively correlated with the level of low-density lipoproteins, triglycerides, total cholesterol [15], disorders of which are the risk factors for AF [1].…”
mentioning
confidence: 99%
“…Even the smallest degree of albuminuria increases risk for cardiovascular diseases and all-cause death [13]. Marushchak M., et al suggested that serum uric acid level is markedly elevated and positively associated with albuminuria in type 2 diabetic patients with comorbid obesity [14]. Furthermore, the degree of albuminuria is positively correlated with the level of low-density lipoproteins, triglycerides, total cholesterol [15], disorders of which are the risk factors for AF [1].…”
mentioning
confidence: 99%